Respuesta :
Way 1
3x^2x = -2
3x^2 - 10x + 2 = 0
Δ= (-10)^2 - 4 * 3 * 2 = 100 - 24 = 76
√Δ = 2√19
x1 = (10 - 2√19)/6 = (5 - √19)/3
x2 = (10 + 2√19)/6 = (5 + √19)/3
3x^2x = -2
3x^2 - 10x + 2 = 0
Δ= (-10)^2 - 4 * 3 * 2 = 100 - 24 = 76
√Δ = 2√19
x1 = (10 - 2√19)/6 = (5 - √19)/3
x2 = (10 + 2√19)/6 = (5 + √19)/3
Answer:
76
Step-by-step explanation:
The discriminant of the quadratic equation [tex]ax^2+bx+c=0[/tex] is given by
[tex]D=b^2-4ac[/tex]
The given equation is
[tex]3x^2-10x=-2\\\\3x^2-10x+2[/tex]
Here, a = 3, b = -10 and c = 2
Therefore, discriminant is given by
[tex]D=(-10)^2-4(3)(2)\\\\D=100-24\\\\D=76[/tex]
Therefore, the discriminant of the given equation is 76.